A versatile star-shaped organic semiconductor based on benzodithiophene and diketopyrrolopyrrole - He,Q; Shahid,M; Panidi,J; Marsh,AV; Huang,W; Daboczi,M; Kim,J-S; Fei,Z; Anthopoulos,TD; Heeney,M (Journal of Materials Chemistry C, 2019)
We report the synthesis of a new star-shaped π-conjugated oligomer, BDT(DPP)4, containing a benzodithiophene core and four diketopyrrolopyrrole arms. The thermal, electrochemical and optical properties are characterized and the results complemented by computational studies. The utility of the molecule is demonstrated in both solar cell and field-effect transistor devices. In the former, BDT(DPP)4 displays low efficiency when used as an acceptor in blends with poly(3-hexylthiophene) but exhibits promising performance as a donor, in blends with either a fullerene or a non-fullerene acceptor. In field-effect transistors BDT(DPP)4 exhibits typical p-type transistor behavior, which is in accordance with its better donor performance in solar cell devices.